Analisis Kalimat "From the River to the Sea, Palestine Will be Free" dalam Perspektif Ilmu Komunikasi - Muhammad Irsyad Sabiq; Neni Yulianita (Jurnal Syntax Admiration, 2024)
The prolonged conflict between Israel and Palestine has produced various narratives and slogans that reflect aspirations, demands, and resistance, one of which is the phrase “From the River to the Sea, Palestine Will be Free.” This slogan is known to have strong political appeal because it holds an explicit message related to Palestinian independence aspirations. From a communication science perspective, it is important to understand how this phrase constructs and communicates meaning and how it is received among diverse audiences. This research aims to analyze the slogan through the perspective of political communication, framing theory, and social identity theory, in order to examine its impact and communication implications in the Israeli-Palestinian conflict. The research method uses a qualitative approach with literature study as the main method. Data collection is done through documentation techniques on various written sources, which are then analyzed through three steps, namely data reduction, data presentation, and conclusion drawing. The results show that the phrase “From the River to the Sea, Palestine Will be Free” is often used in the pro-Palestinian movement as a symbol of freedom aspirations, and serves as an effective communication tool to build identity, mobilize solidarity, and influence public perception regarding complex political issues. The conclusion of this study confirms that the slogan has an important role in shaping political narratives and creating a significant communication impact in the dynamics of the Israeli-Palestinian conflict.